Human resource management in Bangladesh civil service: constraints and contradictions - Siddiquee, Noore Alam (2003)
This paper deals with the organization and management of human resource functions within the Government of Bangladesh. More specifically, it examines and analyzes the current limitations of and future challenges to human resource management in Bangladesh civil service. It demonstrates that despite a few attempts made at reforming and modernizing the civil service during past decades, traditional policies and practices continue to dominate its internal management. The current approach suffers from a multitude of anomalies and deficiencies including the lack of human resource planning, inappropriate staffing policy, discriminatory system of promotion, erratic postings and transfers, absence of any objective performance appraisal system and irrational reward structure. These deficiencies combined with bureaucratic corruption and increasing incidence of politicization adversely affect the quality and performance of civil service. They also pose a great challenge for the future in that they stifle the flowering of merit, professionalism and integrity in the public service. - Reproduced.
Keywords: Human resources development - Bangladesh; Civil service - Bangladesh; Civil service